Implementing a Voluntary, Nonregulatory Approach to Nitrogen Management in Tampa Bay, FL: A Public/Private Partnership - Holly Greening; Bruce D. DeGrove (The Scientific World Journal)
Participants in the Tampa Bay Estuary Program have agreed to adopt nitrogen-loading targets for Tampa Bay based on the water-quality and related light requirements of underwater seagrasses. Based on modeling results, it appears that light levels can be maintained at necessary levels by “holding the line” at existing nitrogen loadings; however, this goal may be difficult to achieve given the 20% increase in the watershed’s human population and associated 7% increase in nitrogen loading that are projected to occur over the next 20 years. To address the long-term management of nitrogen sources, a nitrogen management consortium of local electric utilities, industries, and agricultural interests, as well as local governments and regulatory agency representatives, has developed a consortium action plan to address the target load reduction needed to “hold the line” at 1992 to 1994 levels. To date, implemented and planned projects collated in the Consortium Action Plan meet and exceed the agreed-upon nitrogen-loading reduction goal. An example of the success of the private partnership aspect of this program can be seen in three phosphate fertilizer mining and manufacturing companies with facilities located on Tampa Bay. These companies are participants in the Estuary Program and the Nitrogen Management Consortium to provide support and input for a program that advocates voluntary, nonregulatory cooperation to reach environmental goals.